Efektivitas Simulasi Virtual PhET dalam Pembelajaran Fisika Zat Padat untuk Meningkatkan Pemahaman Konsep Calon Guru Fisika - Heni Rusnayati; Raden Giovanni Ariantara (U-Teach: Journal Education of Young Physics Teacher, 2024)
One of the challenges in learning solid-state physics is that phenomena are microscopic and therefore difficult for students to understand. This study aims to evaluate the effectiveness of using PhET virtual simulations in solid-state physics learning in improving conceptual understanding among prospective physics teachers. The research method used was a quasi-experiment with a one-group pretest-posttest design. The sample consisted of 30 prospective physics teachers from the Universitas Pendidikan Indonesia in Bandung. Concept understanding is measured through a description test. Data were analyzed using the Wilcoxon test and normalized gain to assess the effectiveness of virtual simulation and increase understanding of concepts. The results of the analysis show the positive potential of PhET virtual simulations in increasing the understanding of solid-state physics concepts for prospective physics teachers. Further research is needed regarding factors that can optimize the use of PhET virtual simulations in learning